Relationship of the Degree of Sarcopenia with the Severity of Nonalcoholic Fatty Liver Disease and Cardiometabolic Risk in Adolescents - Yoowon Kwon; Jin A Chung; You Jin Choi; Yoo Min Lee; So Yoon Choi; In Hyuk Yoo; Tae Hyeong Kim; Su Jin Jeong (Life, 2024)
The association between nonalcoholic fatty liver disease (NAFLD) and sarcopenia has been suggested. We investigated sarcopenia’s impact on NAFLD severity and its relationship with cardiometabolic risk in adolescents. We conducted a retrospective study on 122 patients aged 13–18 years and diagnosed with both NAFLD and sarcopenia by laboratory tests, abdominal ultrasound (US), and multifrequency bioelectrical impedance analysis. Sarcopenia was stratified into tertiles based on the skeletal muscle-to-fat ratio (MFR), NAFLD severity was established by the US, and cardiometabolic risk was assessed by the triglyceride–glucose (TyG) index and the atherogenic index of plasma (AIP). Compared with the other patients, those in the lower MFR tertiles exhibited a greater severity of NAFLD (p < 0.001) and significantly higher TyG index and AIP. The independent effect of MFR was observed to have a negative correlation with the severity of NAFLD (p < 0.001). Based on the aforementioned results, the degree of sarcopenia can be considered as one of the risk factors of severe NAFLD and might be an indicator of cardiometabolic risk in adolescents. Weight training to reach the amount of muscle mass could be included in the treatment strategies to improve or prevent NAFLD in adolescents with sarcopenia.